Unforgettable encounters : understanding participation in Italian community archaeology - Ripanti, Francesco, (Access archaeology., 2022)
Whether as excavators and re-enactors, or co-organising research campaigns and outreach activities, the participation of the general public in archaeology has become a well-represented practice, but the impact remains underexplored. Evaluating participation can influence fieldwork practice and enrich the academic discussion on public archaeology.